2015
DOI: 10.1111/ajt.13171
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival in Liver Transplant Recipients Receiving Prolonged-Release Tacrolimus in the European Liver Transplant Registry

Abstract: This study was a retrospective analysis of the European Liver Transplant Registry (ELTR) performed to compare long‐term outcomes with prolonged‐release tacrolimus versus tacrolimus BD in liver transplantation (January 2008–December 2012). Clinical efficacy measures included univariate and multivariate analyses of risk factors influencing graft and patient survival at 3 years posttransplant. Efficacy measures were repeated using propensity score‐matching for baseline demographics. Patients with <1 month of foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
68
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 24 publications
4
68
0
2
Order By: Relevance
“…Data from the ELTR have provided valuable insights in liver transplantation, including information regarding the use of organs from marginal donors, 15 and the development of a risk-analysis model to determine mortality risk of a given procedure in an individual patient. 17 Adam et al 18 recently reported an analysis of data from the ELTR comparing long-term graft and patient survival data for all adult patients transplanted between January 2008 and December 2012 who received tacrolimus-based immunotherapy. The patient groups were stratified by the tacrolimus formulation they received during the first month posttransplant (prolonged-release vs immediate-release formulation).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Data from the ELTR have provided valuable insights in liver transplantation, including information regarding the use of organs from marginal donors, 15 and the development of a risk-analysis model to determine mortality risk of a given procedure in an individual patient. 17 Adam et al 18 recently reported an analysis of data from the ELTR comparing long-term graft and patient survival data for all adult patients transplanted between January 2008 and December 2012 who received tacrolimus-based immunotherapy. The patient groups were stratified by the tacrolimus formulation they received during the first month posttransplant (prolonged-release vs immediate-release formulation).…”
Section: Introductionmentioning
confidence: 99%
“…To prevent center bias, only data from the 21 centers who had been using both tacrolimus formulations were included. 18 Data for 4367 patients were analyzed (528 patients receiving prolonged-release tacrolimus and 3839 patients receiving immediate-release tacrolimus). 18 In this study, the group of patients receiving prolonged-release tacrolimus demonstrated a significantly higher rate of graft survival compared with the group receiving immediate-release tacrolimus over 3 years of treatment (88% vs 80%, respectively; P = 0.01).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations